POETRY METERS (BAHRS), CONCENTRIC CIRCLES (DOIRS) AND THE SIZES OF RUBAI IN THE ARUZ STUDIES OF THE TEMURIDS’ PERIOD - Yusupova, Dilnavoz R. (International Journal of Psychosocial Rehabilitation, 2020)
--In this article in aruz studies of Temurids’ period, particularly, in the evolutionary development of Uzbek and Persian aruz theories the role and specific aspects of such works by Sheikh Akhmad, Alisher Navoi, Zakhiriddin Muhammad Babur, Abdurakhman Jami, Ataulloh Khusaini, Saifi Bukhari were assessed, analyzed and the comparative analysis of these treatises on the surface of bahr, vazn and doira were carried out. Problems regarding the classification of bahrs Makhmud Zamakhshari, the theory of zihofs Abu Jaysh Andalusi, interpretation of juzv and doiras Shams Qays Razi and Nasiriddin Tusi served as theoretical basis for this aruz studies were scientifically reasoned. In aruz studies of the Temurids’ period the difference of zihof, bahr an doiras numbers, directions, characters of treatises and authors’ goals as well as connections of Turkic and Persian aruzes with language laws and rules were grounded. Comparative classification of views on meter specifics of rubai genre and metric peculiarities have been developed. In the treatises of that period on the basis of analyzing the mutalavvun event (device) which arose as an art, it was proved that aruz vazn as a poetic structure had both quantitative and qualitative features in the poetic system.